ANALISIS FAKTOR INTERNAL DAN EKSTERNAL YANG MEMENGARUHI PRODUKTIVITAS PERKEBUNAN SAWIT POLA KEMITRAAN DI KECAMATAN MARO SEBO ILIR KABUPATEN BATANG HARI - Suci Putri Angel Hutasoit; Saidin Nainggolan (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Oil palm plantations constitute one of the most important agricultural commodities inIndonesia, contributing significantly to farmers' livelihoods and regional economic growth. Theproductivity of plasma oil palm farming is closely associated with farmers' internal characteristics,external supporting factors, and the effectiveness of production input utilization. This study aimed to(1) describe the characteristics of plasma oil palm farming, (2) analyze the effects of internal andexternal factors on production input utilization and oil palm productivity, and (3) examine themediating role of production input utilization in improving productivity in Maro Sebo Ilir District,Batang Hari Regency.This study applied a survey approach involving 43 plasma oil palm farmers selected asrespondents. Internal factors included farming experience, participation in the Village UnitCooperative (KUD), ethnic background, willingness to establish partnerships, and openness toexternal influences. External factors comprised Fresh Fruit Bunch (FFB) prices, distance to farminglocations, marketing systems, and access to financial capital. The relationships among variables wereanalyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS).The findings revealed that both internal and external factors significantly and positivelyaffected the utilization of production inputs as well as oil palm productivity. Among these, externalfactors demonstrated a stronger influence than internal factors. In addition, production inpututilization had a significant positive effect on productivity and functioned as a mediating variablelinking internal and external factors with farming productivity. The SEM-PLS results further indicatedthat all proposed hypotheses were statistically supported.These findings suggest that efforts to improve the productivity of plasma oil palm farmingshould focus on strengthening farmers' capacities, enhancing institutional participation, expandingaccess to capital and markets, and promoting the efficient and appropriate use of production inputsto achieve sustainable productivity improvements.